Acalabrutinib in the management of chronic lymphocytic leukaemia. (2nd February 2022) - Dowling, Maura; Kelly, Mary B
Abstract : Chronic lymphocytic leukaemia (CLL) is the most common leukaemia worldwide. This article explores the management of CLL with a particular focus on the role of acalabrutinib in managing patients with CLL under NICE guidelines. Acalabrutinib is a potent bruton tyrosine kinase (BTK) inhibitor. Its use requires careful assessment, monitoring and early intervention to minimise side effects and maintain patients on treatment. Continuity of patient care and promotion of adherence and compliance is essential, particularly in light of the indefinite treatment duration. Patient education is central to therapeutic adherence of oral anti-cancer drugs, and nurses are ideally positioned to educate and support patients with CLL in collaboration with pharmacy colleagues. The benefits of nurse/pharmacy-led oral therapy clinics include continuity of care, consistency in information provision, efficient use of time with patients and carers, improved therapeutic relationships and an enhanced patient experience.